Self-tuning adaptive feedback linearizing output voltage control for AC/DC converter. (December 2015) - Kim, Seok-Kyoon
Abstract: This paper presents a cascade output voltage control law adopting the self-tuning adaptive inner and outer-loop controllers for a AC/DC converter modelled as a nonlinear system. The first contribution is to design the inner and outer-loop controllers updating their control gains to enhance the closed-loop performance, estimating unknown parameters. The second one is to show that the proposed inner-loop controller stabilizes not only current error dynamics but also output voltage dynamics viewed as internal dynamics. The effectiveness of proposed method is shown by performing experiments using a 3-kW AC/DC converter.